Applications of Oxone® in Organic Synthesis: An Emerging Green Reagent of Modern Era. Issue 23 (17th June 2022) - Alvi, Shakeel; Jayant, Vikrant; Ali, Rashid
Abstract: Presently, the major cornerstone of the research community is to develop green as well as sustainable protocols involving inexpensive catalysts and/or reagents without the usage of hazardous solvents under globally friendlier conditions in order to shelter both mankind and environment. Therefore, needless to say, there is always a supreme need to surrogate the older, costlier and unsafe strategies with the novel economically inexpensive and environmental benign ones. To this context, in recent past, oxone® (triple salt), a very cheap oxidizing agent having the chemical formula 2KHSO5  ⋅ KHSO4  ⋅ K2 SO4 and enwrapped with the unique characteristics like easy handling, non‐toxic, safe, eco‐friendly, non‐polluting, stable, and nicely soluble in water, in addition to its utility for large‐scale synthesis etc. Bearing the importance of this versatile reagent in mind, we envisioned to update the recent advances made in this direction. Consequently, in this particular review article, the developments made in the arena of oxone chemistry covering from 2013 to 2020 have been revealed as no report appeared in the literature after a wonderful Chem. Rev. published by the group of Hussain in 2013. Herein, a comprehensive detail of a variety of oxidative transformations along with the complete plausible mechanistic steps have been exposed. For sure, present review would be a very helpful tool to the scientific community not only working in the area of organic synthesis but also to the researchers working in other branches of science and technologies as well. Abstract : This particular comprehensive review article describe the advances (2013‐to‐2020) made in oxone® (a triple salt) chemistry‐ a cheap oxidizing agent with chemical formula 2KHSO5  ⋅ KHSO4  ⋅ K2 SO4, enwrapped with the inimitable features such as easy handling, non‐toxic, safe, eco‐friendly, non‐polluting, stable, and nicely soluble in water. Herewith, a myriad of vital oxidative transformations along with the detailed plausible mechanistic pathways have been exposed. Positively, this review will be a good package for the researchers working in both academia as well as industry.